Implementation of the Open Learning Course for the Islamic Boarding School World (Case Study on Ma'had Al-Ittihad Islami Camplong) - M. Sukron Mahmud Fauzi; Muhammad Wildan Shohib; Muh. Nur Rochim Maksum (al-Afkar, Journal For Islamic Studies, 2024)
This research is based on the development of Information and Communication Technology (ICT), which continues to grow rapidly and unstoppably, so it has a big influence on the spread of Islamic religious knowledge. The open learning course is a system that will be developed for the current era. However, Islamic educational institutions, including Islamic boarding schools, still maintain the classical world of learning? The purpose of this article is to assess the perceptions of managers of Islamic educational institutions, especially at Ma'had Al-Ittihad Islami Camplong, regarding online-based open learning courses. The method used is qualitative with observation and distributing questionnaires to collect data. The results show that the majority of administrators at Ma'had Al-Ittihad Islami Camplong prefer to maintain traditional learning models rather than trying to adopt open learning courses, due to a lack of references and understanding regarding open learning courses. Therefore, socialization efforts are needed regarding open learning courses and the importance of spreading Islamic religious knowledge that is brsanad and mutawatir (continued) in the current context.